IMF conditionality and government education spending: The case of 10 MENA countries - Hassan Sherry; Hussein Zeaiter (Economies, 2024)
This study explores the impact of International Monetary Fund (IMF)-linked conditionality on government education expenditures in the Middle East and North Africa (MENA) region. Understanding the impact of conditional lending by international financial institutions on education spending is important due to the pivotal role education plays in fostering social and economic development. We use country-level panel data encompassing a representative set of 10 MENA countries from 1990 to 2020 and employ a cross-national fixed effects regression model. Our findings suggest that IMF conditionality demonstrates a positive relationship with government education expenditures in the MENA region. The proposed explanation is that the application of IMF policy advice can have a catalytic effect on donor financing, including for education. This indicates that the Fund's financing arrangements in the region can free up fiscal space for social spending, which, in turn, signals a sort of departure of the IMF from the reputation that typically precedes it-its traditional bias for macroeconomic stability irrespective of social costs. We argue that our findings are instructive for policy, especially if one shares the idea that education is a necessary prerequisite for achieving Sustainable Development Goal (SDG) 4: guaranteeing inclusive and equitable quality education and promoting enduring learning opportunities for all.
Keywords: 330; conditionality; education expenditures; fixed effects; IMF; panel data; SDGs